Study on sliding friction and wear behavior of M50 bearing steel with rare earth addition. (October 2022) - Yang, Liqi; Xue, Weihai; Gao, Siyang; Liu, Hongwei; Cao, Yanfei; Duan, Deli; Li, Dianzhong; Li, Shu
Abstract: This study aims to investigate the influence of rare earth (RE) addition on the friction and wear behavior of M50 bearing steel. The results show that RE addition has little effect on friction coefficient, but can reduce wear volume especially under harsh wear conditions. This mainly results from modification of RE elements to primary carbides. M50 steel without RE addition has bigger proportion slenderer rod-like M2 C carbides, which are more likely to cause carbides fracture broken or peeling off, forming bigger wear debris with irregular shape to aggravate the wear. However, M50 steel with RE addition has more spherical MC carbides, which are more easily worn into spherical crowns, forming smaller wear debris which could not increase the subsequent wear. Highlights: Rare earth addition can improve the wear resistance of bearing steel especially under harsh rubbing conditions. Rare earth addition can modify primary carbides. The influencing mechanism of primary carbides on the wear behavior of bearing steel was proposed. Interaction of oxidation film and carbides on the wear behavior was proposed.